(Y,Gd)BO3:Eu red phosphor for dual-layer phosphor structure to enhance the optical performance of white light-emitting diodes - Phan Xuan Le; Le Hung Tien (Institute of Advanced Engineering and Science, 2021)
Among the structures using for fabricating white light-emitting diodes (WLEDs) such as the conformal coating or in-cup geometries, the remote phosphor structure gives the highest luminous efficacy. However, in terms of color quality, its performance is not as good as the others. The red-light compensation has been reported as the effective solution for enhancing the color quality of WLEDs. Hence, this study adopted the idea and applied to the dual-layer phosphor structure. The phosphor used to boost the red color in light formation is (Y,Gd)BO3:Eu particle. The dual-layer remote phosphor structure was simulated with the red (Y,Gd)BO3:Eu phosphor layer above the original yellow phosphor YAG:Ce3+ one. The WLEDs with different correlated color temperatures of 5600 K, 6600 K and 7700K were experimented. Mie-theory and Lambert-Beer law were applied to examine the results. The growth in color rendering index (CRI) and color quality scale (CQS) with the increase of (Y,Gd)BO3:Eu phosphor concentration was observed. Nevertheless, the lumen efficacy would be degraded if the concentration was over a certain number. The information provided in this article is useful for the development of high-power WLED production with greater color quality.